2022
DOI: 10.1111/aec.13213
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary patterns of seasonal changes in species composition of surface‐active arthropods in a South African savannah

Abstract: Surface‐active arthropods have limited dispersal abilities and their abundances are responsive to changes in the environment. Their sensitivity allows for the identification of aspects of environmental variation that are responsible for changes in community assemblages of these arthropods. Limited dispersal abilities allow for changes in the populations of surface‐active arthropods to be linked reliably to changes in their local environment. In this study, we tested the hypothesis that seasonal variation in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…While species richness and abundance of Orthopterans and spiders showed no significant difference between seasons, species richness of beetles and ants was higher in the wet than in the dry season. These results are partially similar to those of Mavasa et al (2022) where similarly the species richness of beetles was greater in the wet season but contrarily, in Mavasa et al (2022), the species richness and abundance of ants showed no significant difference between seasons.…”
Section: Species Richness and Abundance Of Ground-dwelling Arthropods...supporting
confidence: 86%
See 2 more Smart Citations
“…While species richness and abundance of Orthopterans and spiders showed no significant difference between seasons, species richness of beetles and ants was higher in the wet than in the dry season. These results are partially similar to those of Mavasa et al (2022) where similarly the species richness of beetles was greater in the wet season but contrarily, in Mavasa et al (2022), the species richness and abundance of ants showed no significant difference between seasons.…”
Section: Species Richness and Abundance Of Ground-dwelling Arthropods...supporting
confidence: 86%
“…This means there is an increase in the density of arthropods in an ecosystem. In addition, predatory arthropods benefit from the high density of other arthropods of smaller size due to a high number of prey (Mavasa et al 2022).…”
Section: Seasonal Change Influences Resource Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given that arthropods are known to be active mostly during the warmer months (Mavasa et al 2022) and have been reported to correlate positively with precipitation (Uhey et al 2020), we sampled in October 2021. Since the study was focused on surface-active arthropods, the pitfall trapping method was used.…”
Section: Collection and Identification Of Surface-active Arthropodsmentioning
confidence: 99%
“…Since climate and sampling time (i.e., season) does not affect the abundance and richness of arthropods sampled at the savanna and grasslands of sub-Saharan Africa [64,65], plant diversity, stocking rates and grazing intensities could be associated with the varying response of arthropods at different exclosures of KNP [8,10,23,26,33,46,47,[65][66][67]. Therefore, mammal activity and heterogeneity of plants needs to be understood and correlated with assemblages of arthropods to ascertain the direct and indirect impact of mammal grazing on the abundance, species richness and composition of arthropods at KNP.…”
Section: Plos Onementioning
confidence: 99%